2008
DOI: 10.1086/525263
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infection in Patients with Hematological Diseases: Single-Center Study and Review of the Literature

Abstract: Lower RTI, >or=2 SID criteria, and preengraftment are risk factors for RSV-attributed mortality. Polymerase chain reaction may optimize diagnosis and monitoring. Oral ribavirin therapy seems safe, but trials are needed to demonstrate its efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
283
4
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(311 citation statements)
references
References 41 publications
13
283
4
11
Order By: Relevance
“…8 Reported side effects included hemolysis, leukopenia and hyperbilirubinemia. 9,14,16 In our study, no related side effects were observed, which was consistent with previous studies reporting on the use of ribavirin in the hepatitis C infection setting. 17 Recently, Shah et al 6 reviewed and summarized the use of ribavirin from 26 available studies involving adult HSCT patients infected with RSV.…”
Section: Intravenous Ribavirin In Pediatric Hematopoietic Transplantasupporting
confidence: 92%
See 3 more Smart Citations
“…8 Reported side effects included hemolysis, leukopenia and hyperbilirubinemia. 9,14,16 In our study, no related side effects were observed, which was consistent with previous studies reporting on the use of ribavirin in the hepatitis C infection setting. 17 Recently, Shah et al 6 reviewed and summarized the use of ribavirin from 26 available studies involving adult HSCT patients infected with RSV.…”
Section: Intravenous Ribavirin In Pediatric Hematopoietic Transplantasupporting
confidence: 92%
“…3 The frequency of RSV infection in adults is about 2-17% among HSCT recipients. 6,9,10 This incidence is lower than that observed in the present study conducted in infants. Severity is highest in HSCT patients.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Es uno de los virus más frecuentes, con incidencia de 3,4-10% en TOS; 3,5-9% en TPH alogeneico y 0,4-1,5% en TPH autólogo 9 . La progresión a neumonía en estudios recientes es de 55%, con una mortalidad de 7% 9,14 .…”
Section: Epidemiologíaunclassified